Study on the Formation of Antihypertensive Twin Drugs by Caffeic Acid and Ferulic Acid with Telmisartan - Li P; Peng Y; Ma Q; Li Z; Zhang X (Dove Medical Press, 2020)
Pengshou Li,1 Yingying Peng,1 Qixiang Ma,2 Ziyong Li,1 Xiaohua Zhang3 1Department of Food Science and Engineering, School of Food and Drug, Luoyang Normal University, Luoyang 471934, People’s Republic of China; 2Cancer Institute, Fudan University Cancer Hospital and Cancer Metabolism Laboratory, Institutes of Biomedical Sciences, Fudan University, Shanghai 200032, People’s Republic of China; 3Department of Traditional Chinese Medicine and Pharmacy, School of Chinese Materia Medica, Beijing University of Chinese Medicine, Beijing 100102, People’s Republic of ChinaCorrespondence: Xiaohua ZhangSchool of Chinese Materia Medica, Beijing University of Chinese Medicine, No. 11, Bei San Huan Dong Lu, Chaoyang District, Beijing 100102, People’s Republic of ChinaTel/Fax +86-10-8473-8668Email xhua_zhang@sina.comPurpose: This study aimed to synthesize twin drugs from cinnamic acid compounds, caffeic acid (CFA) and ferulic acid (FLA), which can antagonize endothelin-1 (ET-1) with telmisartan through ester bonds. Moreover, the antihypertensive effect of telmisartan and its influence on blood pressure variability (BPV) were enhanced, and the bioavailability of caffeic acid and ferulic acid was improved.Methods: Six twin drugs, which were the target compounds, were synthesized. Hypertensive rats (SHR) and conscious sinoaortic-denervated (SAD) rats were spontaneously used as models for pharmacodynamic research to study the antihypertensive efficacy of these twin drugs. Wistar rats were employed as pharmacokinetic research models to investigate the pharmacokinetics of the target compounds via intragastric administration. Cellular pharmacodynamic research was also conducted on the antagonistic action on Ang II-AT1, ETA and ETB receptor.Results: Compound 1a was determined as the best antihypertensive twin drug and thus was further studied for its effect on BPV. Compared with that of telmisartan, the antihypertensive effect of compound 1a was improved (p< 0.05), and the BPV was reduced (p< 0.05). The bioavailability of caffeic acid and ferulic acid after hydrolysis from twin drugs could be increased to varying degrees, and the differences of the main pharmacokinetic parameters among the different forms of caffeic acid and ferulic acid were statistically significant (p< 0.05 or p< 0.01). Compound 1a had the best antagonistic effect on the Ang II-AT1 receptor. However, the IC50 of Lps-2 was still two orders of magnitude higher than that of the positive drug telmisartan. Hence, the twin drugs worked by metabolizing and regenerating telmisartan and caffeic acid or ferulic acid in the body.Conclusion: The synthesized twin drugs improved telmisartan’s antihypertensive effects, significantly decreased BPV in SAD rats and increased the bioavailability of caffeic acid and ferulic acid. This study serves as a basis for the development of new angiotensin receptor blocker (ARB) in the future and a reference for the development of new drugs to antagonize ET-1.Keywords: ferulic acid, caffeic acid, twin drugs, telmisartan, pharmacokinetics, pharmacodynamics